Mass control of coffee berry borer using red PET‑bottle traps in coffee crop - Fernandes, Flávio Lemes; Picanço, Marcelo Coutinho; Silva, Ricardo Siqueira da; Silva, Ítalo Willian da; Fernandes, Maria Elisa de Sena; Ribeiro, Luan Humberto (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the efficacy of red PET‑bottle traps, containing attractive alcoholic volatile compounds, in the mass control of coffee berry borer (Hypothenemus hampei). The evaluations were carried out in four coffee crops, during two years. Nine hundred PET‑bottle traps, painted red, were distributed in three of the four coffee crops; one crop without traps was used as a control. Holes drilled into berries (%) were determined in these crops. There was a reduction in drilled berries in crops with traps, from the 2007/2008 harvest to the 2008/2009 harvest. The highest coffee berry borer densities in traps was observed in the flowering and small‑green berries stages. The red PET‑bottle trap is efficient in the mass control of the coffee berry borer population, since it reduces the percentage of drilled berries in 57%; however, this reduction is not enough to keep borer densities below the control level.